2015
DOI: 10.18632/oncotarget.3902
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the potential of autophagy in cisplatin therapy: A new strategy to overcome resistance

Abstract: Resistance to cisplatin is a major challenge in the current cancer therapy. In order to explore new therapeutic strategies to cisplatin resistance, we evaluated, in a model of lung cancer (H1299 and H460 cell lines), the nature of the pathways leading to cell death. We observed that H1299 displayed a natural resistance to cisplatin due to an inability to trigger an apoptotic response that correlates with the induction of autophagy. However, pharmacological and genetic approaches showed how autophagy was a mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 79 publications
4
34
0
Order By: Relevance
“…Autophagy is one of the underlying mechanisms of tumor resistance to chemotherapy . In the present study, NB showed moderate sensitivity to PTX, as demonstrated in vivo in a previous study .…”
Section: Discussionsupporting
confidence: 85%
“…Autophagy is one of the underlying mechanisms of tumor resistance to chemotherapy . In the present study, NB showed moderate sensitivity to PTX, as demonstrated in vivo in a previous study .…”
Section: Discussionsupporting
confidence: 85%
“…Apoptosis is the primary mechanism underlying the action of anticancer drugs (17). Autophagy, the intracellular degradation of cytoplasmic components, serves an intricate and paradoxical role in tumor chemotherapy (18,19). The results of the present study indicated that autophagy may act as a pro-survival mechanism in the anticancer action of thioridazine.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast to the studies cited above in support of the cytoprotective function of cisplatin-induced autophagy, work by another team of investigators demonstrated that inhibition of autophagy using either 3-MA or silencing of the autophagy gene, ATG5 , did not significantly alter the influence of cisplatin on viability of H460 cells, indicative of a non-cytoprotective function of autophagy 36 . Furthermore, when autophagy was inhibited either pharmacologically (3-MA) or genetically (silencing of ATG5 ) in p53-null H1299 cells (A549 and H460 cells are wild type in p53), an unexpected reduction of sensitivity to cisplatin was observed, again supporting a cytotoxic function of autophagy.…”
Section: Chemotherapy-induced Autophagymentioning
confidence: 68%